Optimization and Implementation of a Quantitative Western Blot method utilizing maize protein extracts - Jiménez Barboza, Luis Alexis (2021)
Western Blot technique was described for the first time at the end of the seventies and since then, it has been widely used in Molecular and Cellular Biology experiments related to protein studies. This method allows not only the immunodetection of proteins in complex and raw protein extracts and samples, but also the relative amount of a specific protein in a sample. Up to date, there has not been any report of the use and implementation of the Western Blot technique in any laboratory from the Occident Regionof Universidad de Costa Rica. This article aims to become a methodological reference not only for Western Blot implementation but also for preparation and quantification of maize total protein extracts at the Laboratorio de Biotecnología, Sede de Occidente from Universidad de Costa Rica. It is described in detail, from obtaining and preparing maize protein extracts from fresh tissue, to the detection of control protein α-tubulin and the quantification of the signal detected in the immunological assay. Under theconditions here stablished, the Western Blot was semiquantitative for protein loads between 5 and 45μg.